Mind the gaffe : the Penguin guide to common errors in English - Trask, R. L. (Penguin Books London, 2001)
"Mind the Gaffe: The Penguin Guide to Common Errors in English" is a comprehensive reference book authored by R. L. Trask, published by Penguin UK on July 30, 2002. Spanning 320 pages, this guide addresses numerous challenges encountered in writing clear and precise English. Trask offers authoritative insights on a wide range of contentious issues, from politically correct language to the appropriate usage of terms like 'napkin' versus 'serviette'. This resource is designed to assist readers in navigating the complexities of English usage and improving their writing skills.